Development of in vitro propagation of Dimorphorchis lowii (orchidaceae) through semi-solid and liquid culture systems - Juddy E. Jainol (2016)
Dimorphorchis lowii with its spectacular dimorphic flowers is well known to orchid enthusiast. This species belongs to Vandaeae tribe and Aeridinae subtribe. Like most of the other endemic orchids in Borneo island, this species is facing combined threats from habitat loss, habitat degradation, and problems in viable seed production and inefficient conventional vegetative propagation. Therefore in vitro propagation offers an important measure for multiplication and conservation of this species. In this study, protocols for in vitro propagation of D. lowii through semisolid and liquid systems were developed. The effects of basal media (1/2MS, MS, 1/2KC, KC, VW, and Mitra), plant growth regulators (KIN, BAP, TDZ, 2,4-D, NAA, IBA, and IAA), complex additives (banana homogenate, coconut water, tomato juice, peptone, and yeast extract), carbon sources (fructose, glucose, and sucrose), light and dark photoperiods (16-hr light, 24-hr dark, and 24-hr light), and type of leaf segments (leaf tip, middle, and leaf base) on callus induction from leaf explant; protocorm-like-bodies (PLBs) proliferation from callus and shoot development; PLBs proliferation in liquid shake flask culture; shoot multiplication and rooting were investigated. The effect of immersion time on PLB proliferation in temporary immersion bioreactor systems (RITA® and twin-flask (BITO) systems was also investigated. Plantlets were subjected to photoautotrophic and photoheterotrophic conditions prior acclimatization process to study their effects on the survival percentage. Callus induction from leaf tip explant was triggered when half-strength MS medium was used as basal medium and cultures were incubated under 24-hr dark photoperiod. However, the percentage of callus formation was very low at only 2.00%±1.47. TDZ at 3.0 mg/L with NAA at 0.046 mg/L could increase percentage of callus formation. Sucrose at 2.0% (w/v) showed more favourable result with the callus formation at 42.00%±9.60. Leaf tip segment exhibited highest potential in callus formation with the percentage of 50.00%±20.50. KC medium was the most suitable for PLB proliferation and development, yielding the highest percentage of survival at 36.00%±16.52 and 5.83±1.95 new PLBs per proliferated explant. Number of new PLBs was increased to 8.38±2.45 when 2.0 mg/L TDZ was supplemented in KC medium with 60.00%±24.47 PLBs produced shoots. NAA with TDZ at 2.0 mg/L in combination enhanced the number of new PLBs to 10.53±4.50 with 76.00%±23.14 PLBs developed shoots. Addition of 15% (v/v) coconut water In KC medium increased the number of new PLBs to 16.88±6.52 and 70.00%±42.02 developed shoots. Sucrose at 2.0% (w/v) presented the best results producing 11.55±5.63 new PLBs with 72.00%±16.20 produced 10.22±6.17 shoots. The most favourable liquid medium for PLB proliferation in liquid culture system was KC medium with 52.00%±25.88 survival. The percentage of survived explants was increased to 96.00%±5.48 producing 5.13±1.63 new PLBs when 3.0 mg/L TDZ was supplemented in the medium. Auxin was not suitable for PLBs proliferation when applied alone. Complex additive peptone at 0.2% (w/v) was found to be the best in promoting the formation of new PIB with 11.70±5.01. PLB proliferation at 86.00%±10.35 was obtained when sucrose at 1.0% (w/v) added to the medium. Further study to compare the use of complex additive peptone at 0.2% (w/v) and PGR TDZ at 3.0 mg/L to optimize PLB proliferation under light and dark photoperiod was carried out. Peptone was found to stimulate PLBs proliferation with 84.00%±37.03 under 16-hr light photoperiod